2019
DOI: 10.1177/1938640019875322
|View full text |Cite
|
Sign up to set email alerts
|

The Modified Subcapital Metatarsal Osteotomy in the Treatment of Hallux Valgus Recurrence

Abstract: The purpose of the present study is to illustrate the use of a modified subcapital metatarsal osteotomy (MSMO) in the treatment of hallux valgus (HV) recurrence. The article reports the clinical and radiological outcomes of a cohort of 52 consecutive patients presenting with recurrent HV, treated with MSMO. A total of 52 patients (54 feet) underwent operations between May 2010 and November 2015. The mean time of follow-up was 2.5 years (range 5.5-1.0 years), and the mean age was 49 years (range 22-76 years). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Of the 195 osteotomy procedures performed, 23 (11.8%) were identified involving MIS techniques (distal first metatarsal osteotomies)—with percutaneous HV correction using an Reverdin–Isham osteotomy (9) and Bosch–Magnan osteotomy (14). 15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 195 osteotomy procedures performed, 23 (11.8%) were identified involving MIS techniques (distal first metatarsal osteotomies)—with percutaneous HV correction using an Reverdin–Isham osteotomy (9) and Bosch–Magnan osteotomy (14). 15 …”
Section: Resultsmentioning
confidence: 99%
“…Out of the 301 feet, 86 (28.6%) underwent revision with MIS techniques—with 32 undergoing a distal first metatarsal osteotomy 14 and 54 undergoing a modified subcapital metatarsal osteotomy (MSMO). 15 Open revision techniques included 80 scarf osteotomies (26.6%), 51 Lapidus procedures (16.9%), and 84 first MTP joint arthrodesis (27.9%). Four studies indicated if their patients/feet included had had multiple revisions following primary correction of HV prior to the planned revision procedure as part of their study—this included 2 bunionectomies prior to MSMO and 4 bunionectomies prior to first MTP arthrodesis.…”
Section: Resultsmentioning
confidence: 99%
“…Although numerous operative approaches have been proposed aiming at treating HV recurrence, including Scarf osteotomy, 14 modified subcapital metatarsal osteotomy, 15 and lengthening Scarf osteotomy. 16 The recurrence of HV increases the healthy and economic burden of patients, leading to the double hit to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Taking Chevron osteotomy as an example, it has been reported that recurrent asymptomatic hallux valgus appears in both proximal chevron osteotomy (6.5%) and distal chevron osteotomy (2.2%). 13 Although numerous operative approaches have been proposed aiming at treating HV recurrence, including Scarf osteotomy, 14 modified subcapital metatarsal osteotomy, 15 and lengthening Scarf osteotomy. 16 The recurrence of HV increases the healthy and economic burden of patients, leading to the double hit to patients.…”
Section: Comparisons Of Other Approaches and Our Surgical Techniquementioning
confidence: 99%